Pengembangan Model Analisis Non-Performing Loan pada Sistem Pembiayaan Koperasi dengan Sistem Dinamis - Lilia Trisyathia Quentara; Wening Indrati; Erna Rahayu (LPPM STIKI MALANG, 2022)
Cooperatives are microfinance institutions that have developed a lot in society with the aim of improving the people's economy. One of the business processes carried out by cooperatives is to provide financing to their members, with requirements and processes that are much easier than banking. This research was conducted by developing a Stock Flow Diagram (SFD) analysis model for non-performing loans (NPL) in the financing system which applied at KSU Santosa Jambi. The Dynamics System method is used to project the cash flow developments and compare them with the NPL ratio. The results of the study justify that the problem of bad loans has a greater value than the projected profits obtained by cooperatives. In order to mitigation all risks, the 5C analysis that has been used by cooperative management to assess the eligibility of customers’ needs to be reviewed or supplemented with a 7P analysis.